Utilization of QuickBird Satellite Imagery for Green Open Space Mapping and Thematic Map Development in Samarinda, Indonesia - Sri Endayani; Andrew Stefano; Suryana Suryana; Rolly Yulianthi; Karolina Sherly Orianto (Poltanesa, 2026)
Urban green open space (GOS) plays an essential role in maintaining environmental balance and improving the quality of urban life. Accurate spatial information is therefore required to support sustainable urban planning and management. This study aims to utilize high-resolution QuickBird satellite imagery for mapping green open spaces and developing thematic maps in Samarinda City, Indonesia. The research employed visual interpretation and digital image analysis integrated with Geographic Information Systems (GIS) to identify land cover characteristics and classify green open space distribution. Field verification was conducted to improve classification accuracy and validate spatial data. The results demonstrate that QuickBird imagery provides detailed spatial information capable of distinguishing vegetation patterns, urban infrastructure, and land-use variations effectively. The generated thematic maps present updated spatial information that can support urban planning, environmental monitoring, and decision-making processes related to sustainable city development. This approach highlights the effectiveness of high-resolution remote sensing data as a reliable tool for urban spatial analysis and green space management.